2010
DOI: 10.1002/chem.201002111
|View full text |Cite
|
Sign up to set email alerts
|

Multivalency‐Directed Magic‐Ring [2](3)Catenane by Olefin Metathesis

Abstract: [a] Multivalency, [1] as a way to compensate for the weak monovalent interactions in nature, has attracted considerable interest in recent years.[2] Chemists tried to discover the physical basis of multivalency effects based on a thermodynamic model combined with computational studies and found that thermodynamics play a key role as far as multivalent interactions is concerned.[3] The construction of supermolecules by the bottom-up approach to mimic biomacromolecules and their assemblies is one of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Interestingly, it was also found that the trisdialkylammonium macrocycle ions 27 could form a magic ring [2](3)catenane via two olefin metathesis steps. 27 These results show that the combination of multivalency and olefin metathesis provides a powerful tool for the synthesis of complex interlocked molecules. 28…”
Section: Triptycene-derived Tris(crown Ether) Hostsmentioning
confidence: 85%
“…Interestingly, it was also found that the trisdialkylammonium macrocycle ions 27 could form a magic ring [2](3)catenane via two olefin metathesis steps. 27 These results show that the combination of multivalency and olefin metathesis provides a powerful tool for the synthesis of complex interlocked molecules. 28…”
Section: Triptycene-derived Tris(crown Ether) Hostsmentioning
confidence: 85%
“…19 Its three dibenzo-24-crown-8 (DB24C8) rings are positioned in three orientations, which not only allow three dibenzylammonium guests to thread in, but also can accommodate a bent linear trisdialkylammonium strand to facilitate highly efficient synthesis of a [4]pseudocatenane. 20 To introduce more recognition stations into the guest component for the construction of functional catenanes, we proposed that a host with more free volume between the adjacent DB24C8 rings would better meet the requirement of the steric hindrance. Thus, a pyrazine-extended triptycene-derived tris-(crown ether) host eTC was designed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Later work demonstrated it was also possible to produce the same (3)handcuff [2]catenane architecture by starting with an olenterminated tris(benzylammonium) strand. 79 Interestingly, if this strand was already conjoined as a macrocycle and later mixed with the tris(macrocyclic) host, a reversible ring-opening ring-closing metathesis reaction could be stimulated by the addition of Grubbs II catalyst, forming the triply catenated product in high yield. A chiral variation was also reported, 80 where the tris(macrocycle) was modied with (R)-1,1 0 -binaphthyl moieties.…”
Section: Perspectivementioning
confidence: 99%